Efficient stray-light suppression for resonance fluorescence in quantum dot micropillars using self-aligned metal apertures. (10th August 2016) - Hopfmann, Caspar; Musiał, Anna; Maier, Sebastian; Emmerling, Monika; Schneider, Christian; Höfling, Sven; Kamp, Martin; Reitzenstein, Stephan
Abstract: Within this work we propose and demonstrate a technological approach to efficiently suppress excitation laser stray-light in resonance fluorescence experiments on quantum dot micropillars. To ensure efficient stray-light suppression, their fabrication process includes a planarization step and subsequent covering with a titanium mask to fabricate self-aligned apertures at the micropillar positions. These apertures aim to limit laser stray-light in the side-excitation vertical-detection configuration, while enabling detection of the optical signal through the top facet of the micropillars. The beneficial effects of these apertures are proven and quantitatively evaluated within a statistical study in which we determine and compare the stray-light suppression of 48 micropillars with and without metal apertures. Actual resonance fluorescence experiments on single quantum dots coupled to the cavity mode prove the relevance of the proposed approach and demonstrate that it will foster further studies on cavity quantum electrodynamics phenomena under coherent optical excitation.